Ruthless vows : a novel - Ross, Rebecca (Rebecca J.) (Ross, Rebecca (Rebecca J.). Letters of enchantment, 2023)
Two weeks after returning home from the front, Iris and Attie seize another chance to report on Dacre's movements, while Roman, who has lost his memory and is stuck in Dacre's realm, becomes entangled in a mysterious pen pal correspondence, leading to a pivotal decision that could impact the course of the war and his relationship with Iris.